Development of a Project-Based Learning Module on the Theme of Entrepreneurship as an Implementation of the Pancasila Profile Strengthening Project for Grade V Elementary School Students - Marlena, Yeni; Adha, Muhammad Mona; Maulina, Dina; Jaya, M. Thoha Sampurna (Papanda Publisher, 2025)
The implementation of the Pancasila Student Profile Project with the theme of entrepreneurship in schools often faces various problems that can hinder the achievement of learning objectives. One of the main problems is the lack of understanding of teachers and students regarding the concept of entrepreneurship. In order to implement the Pancasila Student Profile Project, this study aims to create a valid, practical, and effective project-based learning module. The sample of this study was 20 students of grade 5 B at SD Global Madani Bandar Lampung. This study is a type of Research and Development (R&D). The research data collection methods include observation, interviews, questionnaires, and documentation. The results of the media expert validation test on the Project-based Learning learning module obtained an average score of 81.25%, material experts obtained an average score of 92.74% with very valid criteria, and language experts obtained an average score of 70.83% with valid criteria. The results of the practicality test of student responses to the Project-based Learning learning module were declared practical with an average score of 92.5%, with a very practical category. The N-Gain test results obtained an average score of 0.73 with high criteria. Conclusion: The Project-based learning module has been proven valid, practical, and effective when implemented at SD Global Madani Bandar Lampung.